PENGELOMPOKKAN WILAYAH KABUPATEN/KOTA BERDASARKAN JENIS KOPERASI DI PROVINSI SUMATERA UTARA - Al Khoiry, Harisah Haquel; Anwar, Samsul (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2024)
Cooperatives are an important aspect in encouraging economic and financial development in Indonesia, including in North Sumatra Province. Therefore, appropriate cooperative development strategies and efforts are needed to support cooperative development in the region. This research aims to group districts/cities in the North Sumatra province based on the 5 existing types of cooperatives, namely consumer, producer, savings and loan, service and marketing cooperatives. This research uses secondary data obtained from the Department of Cooperatives and Small and Medium Enterprises of North Sumatra Province with a total of 5,192 cooperatives. Data were analyzed using the K-means clustering method. The research results show that Medan City as the provincial capital is the region with the most types of cooperatives. Meanwhile, areas far from the provincial capital, like Nias Island, have relatively few cooperatives. The North Sumatra Provincial Government together with the district/city governments need to pay more attention to areas with a minimal number of cooperatives so that the level of community welfare in these areas increases through developing the quantity and quality of cooperatives in the region.